Pectin-rich extracts from olives inhibit proliferation of Caco-2 and THP-1 cells. Issue 8 (19th July 2019) - Bermúdez-Oria, Alejandra; Rodríguez-Gutiérrez, Guillermo; Alaiz, Manuel; Vioque, Javier; Girón-Calle, Julio; Fernández-Bolaños, Juan
Abstract : Pectin-rich olive extracts from a by-product of olive oil production inhibits proliferation of Caco-2 and THP-1 cells, and hemagglutination by galectin-3. Activation of caspase-3 indicates induction of apoptosis. Abstract : Three olive modified pectin extracts have been produced by heat and acid treatment of the major by-product of olive oil production. Their effect on proliferation of the colon carcinoma Caco-2 and the leukemia monocytic THP-1 cell lines has been studied in order to determine possible anti-tumor properties. All extracts inhibited proliferation at some of the concentrations ranging from 1 to 10 mg ml −1 . Interestingly none of the extracts inhibited the growth of confluent Caco-2 cells, showing the specificity of the antiproliferative effect for the transformed Caco-2 phenotype. All the extracts inhibited agglutination of red blood cells by galectin-3, a lectin involved in tumor growth, metastasis, and immune cell regulation that has been proposed as a mediator of the anti-tumor effects of modified pectins. In addition, activation of caspase-3 in THP-1 cells indicates that treatment with the pectin-rich extracts triggers apoptosis. These results point to a possible use as health-promoting food ingredients or supplements.